Haspin Modulates the G2/M Transition Delay in Response to Polarization Failures in Budding Yeast - Galli, Martina; Diani, Laura; Quadri, Roberto; Nespoli, Alessandro; Galati, Elena; Panigada, Davide; Plevani, Paolo; Muzi-Falconi, Marco (Frontiers in Cell and Developmental Biology, 2021)
Symmetry breaking by cellular polarization is an exquisite requirement for the cell-cycle of Saccharomyces cerevisiae cells, as it allows bud emergence and growth. This process is based on the formation of polarity clusters at the incipient bud site, first, and the bud tip later in the cell-cycle, that overall promote bud emission and growth. Given the extreme relevance of this process, a surveillance mechanism, known as the morphogenesis checkpoint, has evolved to coordinate the formation of the bud and cell cycle progression, delaying mitosis in the presence of morphogenetic problems. The atypical protein kinase haspin is responsible for histone H3-T3 phosphorylation and, in yeast, for resolution of polarity clusters in mitosis. Here, we report a novel role for haspin in the regulation of the morphogenesis checkpoint in response to polarity insults. Particularly, we show that cells lacking the haspin orthologue Alk1 fail to achieve sustained checkpoint activation and enter mitosis even in the absence of a bud. In alk1∆ cells, we report a reduced phosphorylation of Cdc28-Y19, which stems from a premature activation of the Mih1 phosphatase. Overall, the data presented in this work define yeast haspin as a novel regulator of the morphogenesis checkpoint in Saccharomyces cerevisiae, where it monitors polarity establishment and it couples bud emergence to the G2/M cell cycle transition.